‘The Eminent English Writer’: Aldous Huxley's "Point Counter Point" and Flann O’Brien's "At Swim-Two-Birds" - Asensio Peral, Germán (Complutense Journal of English Studies, 2018)
Irish writer Brian O’Nolan, better known as Flann O’Brien (1911-1966), among other pseudonyms, published At Swim-Two-Birds, his first novel, in 1939. Early reviewers and contemporary critics alike have hailed it as a metafictional masterpiece, relevant for its mise en abyme narrative structure, lawless characters and mock-epic bravado. However, little attention has been devoted to how such an innovative design was originally conceived by its author in the first place. This article holds the belief that Huxley’s fourth novel, Point Counter Point (1928), stands as a major intertext among the many literary sources O’Brien might have perused when composing At Swim-Two-Birds. Apart from the presence of several direct references to Point Counter Point within O’Brien’s novel, Huxley’s text encompasses metafictional mechanisms that function in a similar way to those at work in O’Brien’s novel. Although there is no factual proof that O’Brien had read Huxley’s novel before he wrote At Swim-Two-Birds, this article endeavours to prove the existence of formal links between both metafictional assemblages by means of a detailed comparative analysis, ultimately concluding that O’Brien had indeed read Point Counter Point before setting out to write his first novel and found the self-referential features of Huxley’s work potentially productive.